Historical Perspectives, State of art and Research Trends of Single Photon Avalanche Diodes and Their Applications (Part 1: Single Pixels) - Cusini, Iris; Berretta, Davide; Conca, Enrico; Incoronato, Alfonso; Madonini, Francesca; Maurina, Arianna Adelaide; Nonne, Chiara; Riccardo, Simone; Villa, Federica (Frontiers in Physics, 2022)
The ability to detect single photons is becoming an enabling key capability in an increasing number of fields. Indeed, its scope is not limited to applications that specifically rely on single photons, such as quantum imaging, but extends to applications where a low signal is overwhelmed by background light, such as laser ranging, or in which faint excitation light is required not to damage the sample or harm the patient. In the last decades, SPADs gained popularity with respect to other single-photon detectors thanks to their small size, possibility to be integrated in CMOS processes, room temperature operability, low power supply and, above all, the possibility to be fast gated (to time filter the incoming signal) and to precisely timestamp the detected photons. The development of large digital arrays that integrates the detectors and circuits has allowed the implementation of complex functionality on-chip, tailoring the detectors to suit the need of specific applications. This review proposes a complete overview of Silicon SPADs characteristics and applications. In this Part I, starting with the working principle, simulation models and required frontend, the paper moves, to the most common parameters adopted in literature for characterizing SPAD performance. In the next Part II, the focus is then posed on the development of SPAD arrays, presenting some of the most notable examples found in literature. The actual exploitation of these designs in real applications (e.g., automotive, bioimaging and radiation detectors) is then discussed.